Spray-on carbon black nanopowder/polyvinylidene fluoride-based solar-thermal-electric generators to power electronic devices - Li, Haitao (2022)
Solar-driven generators are an emerging power generation technology due to the use of sunlight as a green and renewable energy source. However, the complex, tedious, and costly fabrication processes impede large-scale practical application. In this work, we demonstrate a unique solar-Thermal generator for efficient solar-Thermal-electric conversion to enable real-Time, outdoor charging applications using green solar energy. Our solar absorber comprises a cost-effective layer of nanoscale carbon black powders/polyvinylidene fluoride (CB/PVDF) mixture that can be easily sprayed onto the hot end of a commercial thermoelectric device for large-scale fabrication of the solar generator. The solar-Thermal conversion of the CB/PVDF solar absorber can be enhanced by designing hierarchical, micro/nano-sized porous structures for better light penetration and utilization and using an insulating sponge cover to promote heat localization and avert potential environmental fluctuations. These design criteria are necessary to achieve a stable and high electrical output (3.3 mW under 1 sun), even under diverse operating conditions such as different ambient temperatures (0-25 °C) and various sunlight intensities (1-7 sun). As a proof-of-concept application, our generators can be connected in series/parallel and further integrated with a voltage conversion module to enable the efficient and instantaneous charging of modern electronic devices using green solar energy, notably at a charging rate of about 5% per hour. Our unique design is anticipated to expedite the development of an efficient, portable solar generator with the aim to decentralize green power generation, which is beneficial in remote places that do not have access to the electrical grid.